2021
DOI: 10.3390/polym13071036
|View full text |Cite
|
Sign up to set email alerts
|

Product Design by Additive Manufacturing for Water Environments: Study of Degradation and Absorption Behavior of PLA and PETG

Abstract: Additive manufacturing technologies are shifting from rapid prototyping technologies to end use or final parts production. Polymeric material extrusion processes have been broadly addressed with a specific definition of all parameters and variables for all different of technologies approaches and materials. Recycled polymeric materials have been studied due to the growing importance of the environmental awareness of the contemporary society. Beside this, little specific research has been found in product devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 40 publications
2
33
0
2
Order By: Relevance
“…Such phenomenon was observed during a longer analysis made by Buozi Moffa et al [22] where there was also no discoloration registered. Using other types of disinfection for polymers such as photodynamic treatment [23] or microwaves [24] would negatively affect the mechanical properties of obtained parts by extending glass temperature or even plasticizing temperature which causes material degradation [25][26][27]. Such phenomena affect the material structure and also decrease its fatigue properties [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Such phenomenon was observed during a longer analysis made by Buozi Moffa et al [22] where there was also no discoloration registered. Using other types of disinfection for polymers such as photodynamic treatment [23] or microwaves [24] would negatively affect the mechanical properties of obtained parts by extending glass temperature or even plasticizing temperature which causes material degradation [25][26][27]. Such phenomena affect the material structure and also decrease its fatigue properties [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to unfold the biodegradation and decomposition of PLA and its derivatives, mainly for films or injection molded products. In this context, Moreno Nieto et al [ 23 ] reported the design of a 3D-printed oceanographic buoy made from PLA and polyethylene terephthalate glycol (PETG). In their study, the degradation and water absorption properties of 3D-printed PETG and PLA material specimens were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have assessed and outlined the mechanism of hydrolytic degradation of PLA 4–6,8,16–20 . Various parameters that affect hydrolytic degradation, including temperature, humidity, pH, presences of infills, and so forth, have been reported 17,20 .…”
Section: Introductionmentioning
confidence: 99%